Nature-Based Learning and the Development of Naturalistic Intelligence in Early Childhood - Jannah, Supeni Choirul; Trianggono, Mochammad Maulana (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study investigates the effectiveness of nature-based learning through mini garden activities in stimulating naturalistic intelligence in early childhood. Naturalistic intelligence—the ability to recognize, categorize, and interact with elements of the natural environment—is essential to develop during early years. Using a quantitative pre-experimental design with a one-group pretest-posttest model, the study involved 15 children aged 5–6 at a rural early childhood education institution. Data were collected through observations, structured tests, and interviews. Results showed a significant increase in children's ability to identify plant names and parts, classify natural elements, and demonstrate curiosity toward nature. A paired-sample t-test confirmed this improvement (p < 0.001), with a large effect size (Cohen's d = 2.57). Expert validation and reliability testing (Cronbach's ? = 0.84) confirmed the instrument's quality. Findings suggest that nature-based learning is a practical, contextually adaptable approach for enhancing children's cognitive and socio-emotional development through direct environmental interaction.